Analisis Pengaruh Pergantian Manajemen, Opini Audit Tahun Sebelumnya, Financial 37 Distress, Ukuran KAP, dan Ukuran Perusahaan Klien Terhadap Voluntary Auditor Switching: Studi Pada Perusahaan Manufaktur di BEI Periode 2012-2014 - Lesmana, Kevin; Kurnia, Ratnawati (Universitas Multimedia Nusantara, 2016)
Issues about auditor independence is the main cause of enactment of auditor switching regulations. Auditor switching could occured mandatorily because of regulations requiring or voluntarily. Various questions arise when there are several company implemented voluntary auditor switching. This research was aimed to obtain empirical evidence about the effect of management changes, audit opinion of the previous year, financial distress, public accountant firm's size, company's size towards voluntary auditor switching. The object of this research is manufacturing companies listed at Indonesian Stock Exchange (BEI) for the period 2012-2014. Selection of the sample is determined based on purposive sampling method. The sample used in this research are 53 companies listed at Indonesian Stock Exchange for the year 2012-2014.The data used in this study are secondary data, the annual financial statements audited by an independent auditor. Data analysis method used is logistic regression, as the dependent variable is non-metric and the independent variables are mixture of metric and non-metric. The results of this research are management changes, financial distress, company's size have no positive effect towards voluntary auditor switching, and audit opinion of the previous year, public accountant firm's size have no negative effect towards voluntary auditor switching. Keywords: audit opinion, company's size, financial distress, management changes, public accountant firm's size, voluntary auditor switching.